An Investigation of The Integration of Google Classroom in Literature Classrooms The Case Study of Master One Students at Amar Thelidji University - Chettouh, Fatima; Boumediene ,Houda (Faculty of Letters and Foreign Languages Department of English, 2018)
This study is designed to evaluate technology based instruction using Google Classroom program as a pedagogical tool in learning literature. It focuses on the effectiveness of integrating Google Classroom in enhancing and supporting student’s leaning in literature classrooms. Thus, This study aims to examine the effects of Google Classroom on teaching literature, the specific objectives include evaluating students results in learning literature using Google Class, evaluating students satisfaction with the use of Google Classroom program and how it can be an effective tool to improve teaching literature.Yet, it is designed to find an answer to the following question: How can Google Classroom Application be an effective tool to improve and enhance literature learning? However, this work has a descriptive nature that focuses on a quantitative method. The data were collected through a questionnaire addressed to 3 teachers and 10 students of master one at Amar Thelidji University during the academic year 2017-2018. The findings of the study showed that integrating Google Classroom made suitable tool for enhancing learning literature. Therefore, students are more motivated and encouraged to use Google Classroom program